2017
DOI: 10.1002/mnfr.201600625
|View full text |Cite
|
Sign up to set email alerts
|

Complementary cereals and legumes for health: Synergistic interaction of sorghum flavones and cowpea flavonols against LPS‐induced inflammation in colonic myofibroblasts

Abstract: Combining the structurally related cereal flavones and legume flavonols elicit strong synergistic anti-inflammatory response in LPS-stimulated nonmalignant colonocytes, likely by targeting interdependent mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…For example, phenolic acids, such as gallic acid and ferulic acids, were reported to suppress the COX‐2 enzyme, and ferulic acid has been shown to inhibit the production of TNF‐α (Burdette, ). Flavone apigenin and luteolin were reported to inhibit the production of COX‐2, and inhibit the transcription factor (nuclear factor kappa B) that activates the production of these pro‐inflammatory compounds (Agah, Kim, Mertens‐Talcott, & Awika, ; Burdette, ; Funakoshi‐Tago et al., ; Wölfle et al., ). 3‐Deoxyanthocyanidins have also been shown to suppress the production of COX‐2 and PG‐E2 (Makanjuola et al., ).…”
Section: Potential Health Benefits Of Sorghum Grainmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, phenolic acids, such as gallic acid and ferulic acids, were reported to suppress the COX‐2 enzyme, and ferulic acid has been shown to inhibit the production of TNF‐α (Burdette, ). Flavone apigenin and luteolin were reported to inhibit the production of COX‐2, and inhibit the transcription factor (nuclear factor kappa B) that activates the production of these pro‐inflammatory compounds (Agah, Kim, Mertens‐Talcott, & Awika, ; Burdette, ; Funakoshi‐Tago et al., ; Wölfle et al., ). 3‐Deoxyanthocyanidins have also been shown to suppress the production of COX‐2 and PG‐E2 (Makanjuola et al., ).…”
Section: Potential Health Benefits Of Sorghum Grainmentioning
confidence: 99%
“…The inhibitory effects against the pro‐inflammatory compounds is believed to be important for disease prevention. In addition, recent studies have shown that the combination of flavone apigenin and flavonol quercetin, as well as the apigenin‐rich extract from sorghum and quercetin‐rich extract from cowpea, has a strong synergistic anti‐inflammatory effect by enhancing their bioavailability through the suppression of the phase II metabolism and ATP binding cassette membrane transporter function in cellular models (Agah et al., ; Ravisankar et al., ). It has been suggested that the C 2 = C 3 conjugation structure of apigenin and quercetin may play an important role in enhancing the anti‐inflammatory effect (Ravisankar et al., ).…”
Section: Potential Health Benefits Of Sorghum Grainmentioning
confidence: 99%
“…In addition to 3DXA, sorghum has many other polyphenols that may also contribute to its antioxidant activity such as catechins and their derivatives [14]. Although recent research has attempted to gain an understanding of the antioxidant and anti-inflammatory properties of sorghum-derived polyphenols [14,17], underlying molecular mechanisms that contribute to these properties remain unclear. Therefore, the aim of the present study is to investigate the gene expression profiles for potential antioxidant and anti-inflammatory signalling pathways regulated by polyphenols derived from black sorghum in oxidative stress-induced human endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Many phenolic compounds for example phenolic acids, Human Health: A Review such as gallic acid and ferulic acids, from sorghum were reported to suppress the COX-2 enzyme, and ferulic acid has been shown to inhibit the production of TNF-α [64]. Flavone apigenin and luteolin inhibits the production of COX-2, hence, suppressed the transcription factor (nuclear factor kappa B) that activates the production of these pro-inflammatory compounds [64][65][66][67]. Collectively, several phenolic compounds extracted from sorghum grain have been proven to inhibit the production of pro-inflammatory compounds [64,66,68,69].…”
Section: Obesity and Inflammation Preventionsmentioning
confidence: 99%
“…Mice with inflammatory triggered ear edema treated with the phenolic extract from black and red sorghum bran demonstrated significant reduction of ear edema via the down regulation of cyclooxygenase-2 (COX-2) expression, resulting in lower vascular permeability and edema with infiltration of neutrophils [64,69]. In addition, recent studies have shown that the combination of flavone apigenin and flavonol quercetin, as well as the apigenin-rich extract from sorghum and quercetin-rich extract from cowpea, has a strong synergistic anti-inflammatory effect by enhancing their bioavailability through the suppression of the phase II metabolism and ATP binding cassette membrane transporter function in cellular models [65,70]. It is believed that the C2=C3 conjugation structure of apigenin and quercetin may play an important role in enhancing the anti-inflammatory effect [70].…”
Section: Obesity and Inflammation Preventionsmentioning
confidence: 99%